Preservasi naskah kuno pada Yayasan Sastra Lestari berbasis digital - Fina Nurul Zakiyyah; Ninis Agustini Damayanti; Ute Lies Khadijah; Lutfi Khoerunnisa (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2022)
Manuscripts or commonly known as ancient manuscripts are one of the cultural heritage in the form of writing. In the past, ancient manuscripts were written using palm leaves, animal skins, paper, and even stone. When viewed from their physical form, ancient manuscripts are indeed more susceptible to damage due to their fragile nature when compared to other cultural heritages. Factors that can cause damage to ancient manuscripts include physical factors, chemical factors, user ignorance, natural disasters, vandalism, illegal buying and selling of manuscripts, damage by rodents (harmful insects, rats, and rodents), humidity factors, and so forth. Therefore, it is necessary to have activities or processes to be able to preserve ancient manuscripts, namely preservation. One of the preservation efforts to preserve ancient manuscripts is using digitization (the activity of converting ancient manuscripts into digital texts). Yayasan Sastra Lestari is an independent non-profit organization since 1997 that has been engaged in the rescue, preservation, and dissemination of regional literary works of the archipelago from ancient manuscripts to digital-based manuscripts and websites. Based on this background, the purpose of this study is to find out how the manuscript preservation process by Yayasan Sastra Lestari is digital-based and website-based. In addition, this study also aims to find out the challenges, opportunities, and future of Yayasan Sastra Lestari in efforts to preserve digital manuscripts. The research method used is descriptive qualitative. The method of data collection was done through observation and previous research. Observations were made through the official website of the Yayasan Sastra Lestari, which is located at www.sastra.org. The results showed that the digitization process of Yayasan Sastra Lestari went through two major stages, namely pre-digitalization which focused on transliteration and media transfer, and the post-digitization stage in the form of disseminating ancient manuscript information through the website. In addition, the challenges, opportunities, and future faced by Yayasan Sastra Lestari emphasize the external role (academics, teachers, scientists, communities, and others) in improving the quality of digital manuscript preservation.